STUDY OF FISHING GROUND GOMBANG FISHING GEAR IN MESKOM VILLAGE BENGKALIS DISTRICT BENGKALIS REGENCY RIAU PROVINCE - Feby Pandji Syaputra; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTOne of the kind of dominan fishing gear operated by fishermen in the bengkalis strait is gombang.The purpose of this study was determine the fishing ground condition forgombang based on the environmentalcharacteristics, and catch composision.This study was conducted inSeptembertoOctober 2017in the Bengkalis Strait Meskom Village Bengkalis District Bengkalis Regency Riau Province, using survey method.The results showed that the fishing ground was located at 01o32'58,6